Mechanical properties and performance of high volume fly ash roller compacted concrete containing crumb rubber and nano silica - Adamu, M. (Elsevier Ltd, 2018)
This study deals with the development of an environmentally sustainable roller-compacted concrete (RCC) using high-volume fly ash (HVFA) and crumb rubber as partial replacement for cement and fine aggregate respectively, and nano-silica as an additive to cementitious materials. Response surface methodology (RSM) was used to design, develop statistical models, and carry out the optimization for the mixtures using the variables crumb rubber, HVFA, and nano-silica. The responses used for the RSM are compressive, flexural, and splitting tensile strengths. The proposed models demonstrated a high correlation among the variables and responses. An optimised HVFA RCC mix can be achieved by partially replacing 10 fine aggregate with crumb rubber by volume, replacing 53.72 of cement with fly ash by volume, and the addition of 1.22 nano-silica by weight of cementitious materials. Further experimental investigations showed that the HVFA RCC pavement exhibited lower fresh density, Vebe time, compressive strength, splitting tensile strength, flexural strength, modulus of elasticity, abrasion resistance, and impact resistance compared to conventional (control) RCC pavement. These effects further escalate with increase in partial replacement of fine aggregate with crumb rubber. On the other hand, nano-silica increases the mechanical properties and performance of HVFA RCC pavement with or without crumb rubber. This is because of the ability of nano-silica to partially mitigate the negative effect of crumb rubber on the properties of HVFA RCC by densifying the interfacial transition zone between the cement matrix and crumb rubber and filling the pores in the hardened cement matrix. Furthermore, nano-silica partially ignited the pozzolanic reactivity of fly ash at early ages which leads to higher performance of HVFA RCC pavement at early age. Â© 2018 Elsevier Ltd